Physicochemical Analysis of Mymensingh Municipality Sewage Water and Old Brahmaputra River water - Uddin, M; Talukder, S; Hossen, MS; Hossain, MT (Journal of Environmental Science and Natural Resources, 2018)
The study was conducted to investigate the physicochemical properties of the Old Brahmaputra River and Sewage water in Mymensingh Municipality. To perform the study fifty samples were collected from five different stations from the river and surrounding sewage discharge points. The samples were analyzed to determine pH, Electrical Conductivity (EC), Total Dissolved Solids (TDS), Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Lead (Pb) and Cadmium (Cd). The mean value of pH was 7.1 and 6.8 for river and sewage water samples, respectively. Mean EC value was 183 μS/cm and 589.18 μS/cm for river and sewage samples, respectively signifies that EC of all samples were within the acceptable range. 66.32 ppm and 260.36 ppm were the mean TDS value for river and sewage samples, respectively indicates no harm to aquatic lives and irrigation water use. Mean DO and BOD values for river water samples were 4.21 mg/L and 6.02 mg/L, respectively. 3.08 mg/L and 9.98 mg/L were the mean DO and BOD values for sewage water samples, respectively implies that river water is usable for irrigation but sewage water is unfit for it. Mean Pb concentration for river and sewage water samples was 0.428 ppm and 0.467 ppm, respectively. J. Environ. Sci. & Natural Resources, 10(2): 105-108 2017